2021
DOI: 10.1155/2021/6650181
|View full text |Cite
|
Sign up to set email alerts
|

miRNA-mRNA Regulatory Network Reveals miRNAs in HCT116 in Response to Folic Acid Deficiency via Regulating Vital Genes of Endoplasmic Reticulum Stress Pathway

Abstract: Moderate folic acid (FA) intake is an effective strategy that slows colorectal cancer (CRC) progression. However, high consumption of FA may trigger the transition of precancerous tissue towards malignancy. MicroRNAs (miRNAs) are considered to be potential biomarkers of CRC. Thus, identification of miRNAs of dysregulated genes in CRC cells by detailed analysis of mRNA and miRNA expression profile in the context of FA deficiency could substantially increase our understanding of its oncogenesis. mRNA-seq and miR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…The most important interactions in C6 were HSP90B1-CALR (RIA = 0.50), HSPA5-HSP90B1 (RIA = 0.42) and HSPA5-CALR (RIA = 0.39). All three of this genes are regulated by ATF6 (see REACTOME, also ( 43 )). In Ciliated cells, several genes also showed frequent interactions with RSPH1 such as RSPH1-RUVBL1 (RIA = 0.22) and RSPH1- IGFBP7 (RIA = 0.18).…”
Section: Resultsmentioning
confidence: 99%
“…The most important interactions in C6 were HSP90B1-CALR (RIA = 0.50), HSPA5-HSP90B1 (RIA = 0.42) and HSPA5-CALR (RIA = 0.39). All three of this genes are regulated by ATF6 (see REACTOME, also ( 43 )). In Ciliated cells, several genes also showed frequent interactions with RSPH1 such as RSPH1-RUVBL1 (RIA = 0.22) and RSPH1- IGFBP7 (RIA = 0.18).…”
Section: Resultsmentioning
confidence: 99%
“…It has been demonstrated that the upregulation of miR-23a-3p suppressed oxidative stress in ischemic brain injury using a mouse model [ 27 ]. Moreover, it has been shown that folic acid deficiency might upregulate miR-30d-5p to inhibit the expression of key genes in the endoplasmic reticulum stress pathway in colorectal cancer cells [ 28 ]. This suggests the possible involvement of miR-30d-5p in the cellular response to folic acid deficiency in SB pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…MicroRNAs are a type of short noncoding RNAs (~22 nucleotides) important in regulating cellular response and function, including UPR [69,70]. Several miRNAs such as miR-30d [71,72], miR-199a-3p or miR-199a-5p [73], miR-214 [73], miR-379-5p [71,72], and miR-7112-3p [74] were reported to target Grp78, thus affecting protein folding and leading to ERS. The understanding of the involvement and role of miRNA in tocotrienolmediated ERS is very limited.…”
Section: Novel Approaches In Studying Tocotrienol-mediated Ersmentioning
confidence: 99%